Evaluation and comparison of quality of life and its related factors in pre-dialysis and hemodialysis patients - Mohammad Reza Tamadon; Sajad Hasani; Ensieh Farhidzadeh; Majid Mirmohammadkhani (Society of Diabetic Nephropathy Prevention, 2018)
Introduction: Chronic kidney disease (CKD) in advanced stages leads to some changes in lifestyle, health status, and personal functioning and consequently affects the patients' quality of life. Objectives: Given the high prevalence of CKD in the country, this study aimed to determine quality of life and its related factors in this group of patients. Since there has been low focus on quality of life in pre-dialysis stage, this study compared the two groups of pre-dialysis and hemodialysis patients regarding quality of life. Patients and Methods: This descriptive analytical research was conducted as a cross-sectional study. Using convenience sampling method, we selected a total of 60 kidney failure patients in pre-dialysis stage that referred to nephrology clinics in Semnan and 60 hemodialysis patients who referred to the dialysis center of Kosar hospital in Semnan. Using SF-36 questionnaire and a demographic form, the required data was collected via interviews. Results: The results showed that the majority of patients had a moderate quality of life. Concerning demographic variables, quality of life had a significant relationship with age, gender, marital status, number of children, employment status, education level, income level, hemoglobin, underlying disease, duration of disease, and duration of dialysis. Moreover, patients in pre-dialysis stage had a better score than hemodialysis patients regarding the overall quality of life (P≤0.05). Conclusion: This study showed, a design a framework for care services provided by medical staffs and supports provided by insurance organizations and other institutions is necessary. The framework must help to improve quality of life of patients and prevent the deterioration of quality of life in advanced stages of the disease.